The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1080/1461669042000327045
|View full text |Cite
|
Sign up to set email alerts
|

Trust in food safety in Russia, Denmark and Norway

Abstract: In this paper we argue that institutional conditions should be taken into consideration when consumers trust in food safety is analysed. Our survey results demonstrate that levels of trust in food safety varies considerably across our three selected countries: Russian consumers expressing the lowest level of trust, Norwegian consumers the highest and Danish consumers expressing levels of trust in food safety which were in between. We find empirical evidence in all countries that consumers trust in food safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 17 publications
0
57
0
1
Order By: Relevance
“…Zinn (2008) Archived at Flinders University: dspace.flinders.edu.au along with others (see Brown 2008 andMollering 2001) argue that trust has both a rational component which arises from experience of the source and an irrational component based on instinct and emotion. Diminishing trust in the food supply in other contexts has been associated with major food scares (Kjaernes et al 2007;Berg et al 2005;Berg 2004). Australia has not experienced a food scare of the magnitude of, say, BSE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinn (2008) Archived at Flinders University: dspace.flinders.edu.au along with others (see Brown 2008 andMollering 2001) argue that trust has both a rational component which arises from experience of the source and an irrational component based on instinct and emotion. Diminishing trust in the food supply in other contexts has been associated with major food scares (Kjaernes et al 2007;Berg et al 2005;Berg 2004). Australia has not experienced a food scare of the magnitude of, say, BSE.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have argued for diminishing trust in the food supply in light of food scares which have damaged trust in actors in the food chain (Biltgard 2008;Masood 1999;Kjaernes et al 2007;Berg et al 2005;Berg 2004). The Trust-in-Food survey conducted in seven European countries demonstrated that while retailers are trusted to maintain the safety of food products, other food actors including farmers, food authorities, the food manufacturing industry and the media, are distrusted by food consumers (Poppe & Kjaernes 2003).…”
Section: Trust In the Food Supplymentioning
confidence: 99%
“…While scholars have treated governmentality as an embodied experience (Thompson and Hirschman, 1995;Thompson, 2004;2005), what has not been sufficiently addressed is the interrelationship between the national cultural context and consumers' experiences of their bodies. While there are certain similarities of late modern experiences of one's own body due to the common heritage of Western thought, the particular discourses concerning bodies differ within particular cultures, not least because of a diverging historical development.…”
Section: Body and Consumer Culturementioning
confidence: 99%
“…The production of meaning, however, is far from situational and takes place in relation to a generalized repertoire of meanings in society (Halkier et al, 2007, p. 382). In a similar vein, Berg et al (2005) analyzed the institutional conditions in four different settings in connection with consumers' trust in food safety. On the other end of the spectrum, the work of Lotte Holms and Helle Kildevang (1996) deals with everyday body-related considerations, yet does not take into account their embeddedness in macro-level structures.…”
Section: Body and Consumer Culturementioning
confidence: 99%
“…Previous research tends to focus on individual-level explanations, identifying several demographic and ideological predictors of risk concern, for example gender, education, perceived control, and institutional trust (Siegrist and Cvetkovich 2000;Slovic 1987). Less research investigates contextual influences on risk perception, but qualitative studies suggest that the structure of food provisioning systems, divisions of regulatory authority, and media coverage could contribute to national variations by shaping public expectations about risk management (Berg et al 2005;Kjaernes, Harvey, and Warde 2007). Much of this research examines only a handful of countries, however, raising questions about generalizability.…”
Section: Introductionmentioning
confidence: 99%